Embalagens ativas e inteligentes: tendências e projeções - Cândido, Antônio Henrique Melo (Universidade Federal de São Carlos, 2023)
Packaging is a technique that involves wrapping or protecting products for distribution, storage, commercialization, and use. In addition to containing the product, packaging also identifies, describes, protects, displays, promotes, and maintains properties and quality. Food packaging can be specifically defined as the packaging that protects against physical, chemical, and biological sources of contamination or adulteration. Active and intelligent packaging are two forms of commercialization that have the primary role of extending the shelf life of food products, thus reducing losses from expired or spoiled food. Unlike conventional packaging, active packaging employs technology that intentionally releases or absorbs compounds from the food or the free space in the packaging, thereby extending the products' shelf life by interrupting degradative reactions such as lipid oxidation, microbial growth, and moisture gain and loss. Intelligent packaging, on the other hand, communicates with consumers and other intermediaries throughout the entire commercialization chain. It is estimated that these two types of packaging will drive this sector, as the number of the world's population exceeds eight billion, and smart strategies for the production, distribution, and commercialization of food products become essential for society's development in the 21st century. The objective of this undergraduate thesis was to describe the current status of active and intelligent packaging within the food sector, highlighting the types already in use, and relate their functioning mechanisms to chemical engineering. Through a comparative contextualization between conventional and intelligent packaging, we sought to identify economically viable application trends that project the future of this form of food commercialization.
Active and smart packaging: trends and expectations
Keywords: Embalagens; Embalagens inteligentes; Embalagens ativas; ENGENHARIAS::ENGENHARIA QUIMICA